Mechanical and Vibrational Properties of ZnS with Wurtzite Structure： A First-Principles Study - 虞游 陈春林 赵国栋 郑小林 朱兴华 (Chinese physics letters, 2014)
We perform a first-principles study of the mechanical and vibrational properties of ZnS with a wurtzite structure. The calculated elastic constants by using a pseudopotential plane-wave method agree well with the experimental data and with the previous theoretical works. Based on the elastic constants and their related parameters, the crystal mechanical stability is discussed. Calculations of the zone-center optical-mode frequencies including longitudinal-optical/transverse-optical splitting, by using the density functional perturbation theory, are reported. All optical modes are identified, especially B1 modes, and agree with Raman rneasurements.